The International Criminal Court and responsibility for mass atrocities: Can JCE enhance capacity to hold masterminds accountable? - Aquilina, Kevin (Contemporary justice review, 2024)
Mass atrocity crimes constitute a grave affront to international peace and security as well as to human rights. Due to their deep reach in society, they also constitute a very major social predicament. It is undignifying to allow perpetrators of these crimes to be left un-investigated or unpunished. This paper considers how behind the scenes high-ranking military and political indirect perpetrators of mass atrocity crimes should be adjudged guilty of collective criminal responsibility. One mode of collective criminal responsibility – Joint Criminal Enterprise (JCE) – is hereby analysed. Considering the International Criminal Court’s praxis in rejecting certain approaches to JCE, we propose two amendments to the ICC’s Rome Statute, namely: incorporating JCE into Article 25(3)(a) to include acts through another person via JCE, and adding provisions to define elements of Article 25A to guide the Court’s interpretation. This will enable the ICC to apply JCE like the international ad hoc tribunals have done in the past, in the process enhancing the capacity to hold masterminds accountable and buttressing the causes of restorative and social justice in societies grappling with the effects of mass atrocities.